Peran Regulasi dalam Mendorong Pengawasan ESG di Perusahaan Indonesia dan Kesiapan Infrastruktur Hukum - Putri Zakia, Safira; Novelita Saharany, Alisa; Aulia Rohma Gafar, Adinda (UNIVERSITAS SERAMBI MEKKAH, 2024)
This article delves into the multifaceted role of regulatory frameworks in enhancing Environmental, Social, and Governance (ESG) oversight within Indonesian corporations, while critically assessing the adequacy of the existing legal infrastructure to support the implementation of sustainable practices. As global pressure mounts on companies to adhere to ESG principles, Indonesian firms face unique challenges, including a fragmented regulatory environment and varying levels of awareness among stakeholders regarding the importance of ESG compliance. This study investigates the alignment of national regulations with international ESG standards and evaluates the effectiveness of current legal mechanisms in promoting accountability and transparency. Furthermore, it analyzes the implications of insufficient regulatory guidance on corporate governance and the potential for investor confidence to wane in the absence of a cohesive legal framework. Through qualitative analysis and case studies, the research highlights best practices in ESG implementation and proposes actionable recommendations for policymakers to enhance the regulatory landscape. The findings underscore the urgent need for a holistic regulatory approach that integrates ESG considerations into the core governance framework, ultimately fostering sustainable business development in Indonesia.